Photovoltaic–thermal advanced technology for real applications: Review and case study - Jinhwan Oh; Sangmu Bae; Hobyung Chae; Jaeweon Jeong; Yujin Nam (Energy Reports, 2023)
This study analyzes research trends on photovoltaic–thermal (PVT) systems used in buildings. The applications of PVT systems are also classified into system design, material and fluid types, and operating methods. Although many studies proposed new types of PVT systems and applications to improve system performance, there are few reports on the design and operating methods for the system, which consists of the PVT system and hot water storage tank in real-scale buildings. Therefore, our research team conducted a quantitative evaluation of a small household with a PVT system and hot water storage tank installed, according to design factors. The results of the parametric study showed that electricity production was more sensitive to changes in system capacity than those in heat production. By contrast, the change in heat production was dominant in response to the change in the installation angle and load profile of domestic hot water. Through energy simulation, it was found that the PVT system could provide 95% of the annual thermal energy for the domestic hot water consumption of the target buildings.